Fucoidan-functionalized polysaccharide submicroparticles loaded with alteplase for efficient targeted thrombolytic therapy. (October 2021) - Zenych, Alina; Jacqmarcq, Charlène; Aid, Rachida; Fournier, Louise; Forero Ramirez, Laura M.; Chaubet, Frédéric; Bonnard, Thomas; Vivien, Denis; Letourneur, Didier; Chauvierre, Cédric
Abstract: Intravenous administration of fibrinolytic drugs is the standard treatment of acute thrombotic diseases. However, current fibrinolytics exhibit limited clinical efficacy because of their short plasma half-lives and might trigger hemorrhagic transformations. Therefore, it is mandatory to develop innovative nanomedicine-based solutions for more efficient and safer thrombolysis with biocompatible and biodegradable thrombus-targeted nanocarrier. Herein, fucoidan-functionalized hydrogel polysaccharide submicroparticles with high biocompatibility are elaborated by the inverse miniemulsion/crosslinking method. They are loaded with the gold standard fibrinolytic – alteplase – to direct site-specific fibrinolysis due to nanomolar interactions between fucoidan and P -selectin overexpressed on activated platelets and endothelial cells in the thrombus area. The thrombus targeting properties of these particles are validated in a microfluidic assay containing recombinant P -selectin and activated platelets under arterial and venous blood shear rates as well as in vivo . The experiments on the murine model of acute thromboembolic ischemic stroke support this product's therapeutic efficacy, revealing a faster recanalization rate in the middle cerebral artery than with free alteplase, which reduces post-ischemic cerebral infarct lesions and blood-brain barrier permeability. Altogether, this proof-of-concept study demonstrates the potential of a biomaterial-based targeted nanomedicine for the precise treatment of acute thrombotic events, such as ischemic stroke.